PERCEPTION OF AGRICULTURE STUDENTS IN MAHARASHTRA TOWARDS FARMING AS OCCUPATION - SHARVARI PATIL; RUTU YEWALE (The Journal of Research ANGRAU, 2024)
The study examined how 290 agriculture students in Maharashtra perceived farming as an occupation in the year 2024. Researchers looked at various economic, Socio-Cultural, personal, physical, and psychological criteria to gauge how agricultural students felt about farming as a career. The study’s conclusions showed that an astounding 50.7 per cent of students believed that farming is associated with poor income, and 78 per cent thought that farmers committed suicide because of their poor income. According to the survey, most students agreed that farming is the occupation with the lowest standing in society, and farmers are not regarded as professionals. Most respondents agreed that farming involves a significant amount of physical work. Because farmers are exposed to extreme weather conditions, a large percentage of respondents (50.7%) agreed and (26.6%) strongly agreed that farmers are always at risk. Many respondents agreed that farmers enjoy working hard. Most respondents agreed that using cutting edge techniques and technology may boost agricultural income. 53.1 per cent of respondents felt that feeding others is a fulfilling aspect of farming. Students have offered insightful comments on the topic of income sufficiency. Among respondents, 50.7 per cent agreed, and 22.4 per cent strongly agreed that farming generates enough revenue to cover a family’s fundamental necessities. In contrast, 50.3 percent of respondents agreed that suicide was a result of unmet fundamental necessities and financial obligations. Therefore, policies that encourage students to work in agriculture and do it in a contemporary manner must be developed.